2021
DOI: 10.2147/ott.s330341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of ADAMTS19, BMP7, SIM1, and SFRP1 Promoter Methylation in Renal Clear Cell Carcinoma

Abstract: Background: Clear cell renal cell carcinoma (ccRCC) is the most common subtype of kidney tumors, accounting for the majority of deaths from genitourinary cancers. The currently used nomograms for predicting patient outcomes are based on clinicalpathological characteristics only; however, a significant number of ccRCC survivors with similar radiological and histological features still demonstrate a different clinical course of the disease. This study aimed at the identification of novel DNA methylation biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…37 Kubiliute et al reported that the DNA methylated status of the three gene panel of ADAMTS19, BMP7 and SFRP1 was predictive of a poorer overall survival in clear cell renal carcinoma. 38 The relationship between BMP7 expression and overall survival in the current study suggests that BMP7 expression could potentially be used as a prognostic tool in ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 60%
“…37 Kubiliute et al reported that the DNA methylated status of the three gene panel of ADAMTS19, BMP7 and SFRP1 was predictive of a poorer overall survival in clear cell renal carcinoma. 38 The relationship between BMP7 expression and overall survival in the current study suggests that BMP7 expression could potentially be used as a prognostic tool in ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 60%
“…These functions are associated with cellular and neoplastic growth, and interestingly, the peak expression times for these genes are different in healthy livers and tumors, as shown in Figure 5 D . Another notable difference is a set of cancer-associated genes that are significantly rhythmic in tumor ( 31 , 32 , 33 , 34 , 35 , 36 , 37 ) only; examples of these are shown in Figure 5 E . For this class of genes rhythmic in tumor only, we were interested to see if protein expression was rhythmic in tumor only.…”
Section: Resultsmentioning
confidence: 99%
“…Of the genes, “rhythmic in tumor only” were 95 genes classified as “multicellular organism development” or “cell differentiation.” These included genes associated with carcinogenesis such as Aurkb, Wnk2, Wnt11, Wnt7b, Notch3, Sim 1, and Sim2 ( Figs. 5 E and S2 ) ( 31 , 32 , 33 , 34 , 35 , 36 , 37 ). Importantly, the “rhythmic in tumor only” proliferation genes exhibited peak expression times (ZT0 to ZT8) that differed from the peak expression times of “rhythmic in liver only” nucleic acid metabolism genes (predawn and predusk, Fig.…”
Section: Discussionmentioning
confidence: 99%